2017
DOI: 10.3390/plants6020020
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Drought Stress in Brassica Seedlings with Exogenous Application of Ca2+ and H2O2

Abstract: Drought is one of the most common abiotic stresses, affecting the growth and productivity of crop plants globally, particularly in arid and semi-arid regions. Different strategies are used to mitigate the impact of drought among crop plants. Exogenous application of different substances are known to decrease the effects of various abiotic stresses, including drought stress. The aim of this study was to evaluate the effect of Ca2+ and H2O2 in developing drought stress tolerance in Brassica napus “Bulbul-98” see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…The H 2 O 2 increase in G. max during drought stress was consistent with a study on the response of Triticum aestivum to drought stress (Elkeilsh et al 2019). EL (%) was markedly increased in G. max under drought stress, which has been widely reported in crops (Assaha et al 2016;Khan et al 2017). In previous studies, changes in root activity were not reported with HBR application under drought stress.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The H 2 O 2 increase in G. max during drought stress was consistent with a study on the response of Triticum aestivum to drought stress (Elkeilsh et al 2019). EL (%) was markedly increased in G. max under drought stress, which has been widely reported in crops (Assaha et al 2016;Khan et al 2017). In previous studies, changes in root activity were not reported with HBR application under drought stress.…”
Section: Discussionsupporting
confidence: 89%
“…Drought negatively influences plant growth and yield, especially in drought-prone areas of the world (Hasan et al 2020). The prolongation of drought may lead to critical physiological and developmental changes in plants (Khan et al 2017;Hasan et al 2019). Drought causes various metabolic and physiological abnormalities in plants such as loss of cell turgor, cell shrinkage, photosynthetic reduction, and imbalance in mineral content (Choudhury et al 2017;Dubey et al 2018;Yang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S acts as an important signaling molecule during plant response to biotic and abiotic stresses [21,22]. Moreover, H 2 S also acts as an antioxidant, and improves the performance of plants under stress conditions [23,24,25]. H 2 S plays a significant role in various physiological and biochemical processes, including seed germination, morphogenesis, photosynthesis, and flowering [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…production, considered as a major abiotic stress that has affected plant growth rate and development [3][4][5]. Due to changing climatic conditions, water shortages have become more apparent not just in arid regions, but humid regions as well [6].…”
mentioning
confidence: 99%